2021
DOI: 10.1108/jiabr-09-2020-0282
|View full text |Cite
|
Sign up to set email alerts
|

Does trust in zakat institution enhance entrepreneurs’ zakat compliance?

Abstract: Purpose Although zakat is a principal way to redistribute wealth, a unique practice designed to achieve a sustainable Islamic economic and social system, zakat institutions and agencies in most Muslim countries still suffer from the perplexing issue of low zakat collections, ascribing this to the level of compliance among zakat payers. To provide more insight into this lacuna, this study aims to examine the role of trust in zakat institution through the relationship between socio-economic determinants (i.e. re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 52 publications
2
29
0
1
Order By: Relevance
“…In Yemen, according to Zakat Law No. 2 of 1999, the Zakat authority (GDZO) is the only responsible body for administering and collecting Zakat funds from individuals and companies, while any Zakat payment does not go through this authority, it is considered unlawful behaviour (Bin-Nashwan et al. , 2021b).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In Yemen, according to Zakat Law No. 2 of 1999, the Zakat authority (GDZO) is the only responsible body for administering and collecting Zakat funds from individuals and companies, while any Zakat payment does not go through this authority, it is considered unlawful behaviour (Bin-Nashwan et al. , 2021b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because all Yemenis are Muslims, there is the potential for huge Zakat funds; however, in reality, national collection through the GDZO is still far below what is expected. One of the reasons for this phenomenon is a lack of confidence in the authority, as Bin-Nashwan et al. (2021b) argued.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, trust was found to have a significant relationship with entrepreneurs’ zakat compliance behaviour. In the numerous behavioural studies that highlighted the importance of trust in various contexts, it was found to be a significant factor influencing donation behaviour (MacMillan et al, 2005; Sargeant and Lee, 2004; Alhidari et al, 2018), tax compliance (Kogler et al, 2013; Torgler, 2005) and zakat compliance behaviour (Tsalas et al, 2019; Bin-Nashwan et al, 2021b). In the current study, trust shows less than the recommended minimum effect size representing a “practically” significant effect for social science data.…”
Section: Discussion and Research Implicationsmentioning
confidence: 99%
“…Additionally, it has been found that business zakat constitutes about 65% of all zakat collections in Algeria. Thus, determinants of business zakat compliance should be understood before suitable policies can be formulated (Bin-Nashwan et al, 2021a, 2021b). Improving business zakat collection is necessary since it is a very important tool for fighting poverty and achieving social justice.…”
Section: Introductionmentioning
confidence: 99%